Assessment of Knowledge and Awareness Towards Sustainable Development and Well-being of Rural Area: A Case Study of Kg. Benoni, Papar, Sabah - Mohd Redzuan, Farah Nastasya; Jailani, Junaidah (Recent Trends in Civil Engineering and Built Environment, 2023)
The Sustainable Development Goals (SDGs) requires everyone’s participation, including the general public; yet, Malaysian residents’ understanding of the government’s SDGs objective remains low. The purpose of this study was to determine the level of knowledge and awareness of the SDGs, as well as the community’s well-being in the rural area at Kg. Benoni, Papar, Sabah. The community of Kg. Benoni was given survey questionnaires based on knowledge, awareness, and perception, and the data were analyzed using SPSS version 26. Descriptive statistics showed that the respondents have high knowledge and awareness of SDGs and their perceptions of current development were mainly positive. The relationship between variables was determined using Spearman’s rho coefficient correlation. The results showed negatively moderate relationship between knowledge and awareness (r = -.315, N = 167, p = .00) and strongly positive relationship between well-being and awareness (r = .746, N = 167, p = .00). Thus, strategic interventions should be undertaken to include the public in sustainable development through a community-based campaign that involves the rural population in making decisions concerning rural problems.